Integrated Structure of the Development of the Turbine-Generator Set of a Block-Modular Type - Shevchenko, Valentine Vladimirovna; Minko, Alexandr Nikolaevich (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2017)
Data of the theoretical analysis of the development of off-line turbine-generator electric power sources abroad have been given. A structure of the development of the turbine generator set consisting of the single-stage active turbine, cylindrical gear reducer and the turbine generator was formulated. For the single-stage active turbine the following initial parameters, in particular the pressure, flow rate, steam temperature and expected turbine power were adopted. The main design indices of the turbine structure are the optimal ratio of steam flow rates, the heat drop in the stage, nozzle block channel area, nozzle block cascade flow outlet angle, stage rotor diameter, stage rotor blade-to-blade space channel area, a number of the blades of stage rotor and the blade outlet angle. For the cylindrical gear reducer the following initial parameters were selected: circumferential velocity of driving and driven shafts and a number of drive stages. We proposed to define the following main design indices for the reducer structure: the gear diameters of driving and driven shafts of the reducer, a number of teeth for the gears of driving and driven shafts of the reducer and the value of contact stresses that arise at the interface of driving and driven shafts of the gear. The following indices were adopted for the turbine generator: total power, rated voltage, rated current, and the rotor speed and power coefficient. The ideas on the state of design problems of turbine-generator sets of this type were suggested.